A modified staging system for chronic osteomyelitis - Marais, Leonard Charles (J Orthop, 2015)
AIMS: To investigate the short-term outcome of treatment of chronic osteomyelitis where management was based on a refined host stratification system. METHODS: A retrospective review of 109 adult patients with chronic osteomyelitis. RESULTS: At a minimum follow-up of 12 months (range 12–36) we observed an overall success rate of 89.9% (95% CI: 82.7–94.9%). There was no statistically significant difference in success rates by host status (p-value = 0.201). CONCLUSION: By integrating the redefined host status and treatment strategy, we were able to achieve comparable short-term outcomes in both low and high-risk cases while maintaining a low rate of amputation.